THE CONCEPTS OF CAPITAL AND INCOME IN THE REGULATION OF PUBLIC UTILITIES. - Bauer, John (The Accounting Review, 1937)
The article discusses fundamental distinction in the concepts of capital and income as employed by economists and accountants with regard to ordinary business and as applied to public-utility regulation. This concept appears in two kinds of undertakings. The first is concerned with private interests, and the second with public as well as private interests. In the one, there is the underlying consideration and measurement of private industrial values and income, in the other, there is basically the determination and administration of public rights in properties dedicated to special public use. The concepts have been developed and are generally used as private business categories. They are associated with private economy, and so represent "capitalism" which generally prevails as the dominant system in the national economic organization. Along with the system of private business or capitalism, there has been also parallel advance of publicly or governmentally organized economic activity. There has also been progressive demarcation of private organization with respect to public interest.